Mechanics of flight - Kermode, Alfred Cotterill (Pearson, 2013)
Mechanics of Flight is an ideal introduction to the basic principles of flight for students embarking on courses in aerospace engineering, student pilots, apprentices in the industry and anyone who is simply interested in aircraft and space flight. Written in a straightforward and jargon-free style, this popular classic text makes the fascinating topic of aircraft flight engaging and easy to understand.